2014
DOI: 10.25225/fozo.v63.i2.a8.2014
|View full text |Cite
|
Sign up to set email alerts
|

Home range size and spatio-temporal dynamics of male sika deer (Cervus nippon; Cervidae, Artiodactyla) in an introduced population

Abstract: BioOne Complete (complete.BioOne.org) is a full-text database of 200 subscribed and open-access titles in the biological, ecological, and environmental sciences published by nonprofit societies, associations, museums, institutions, and presses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 44 publications
1
7
0
Order By: Relevance
“…So in the period 2003 -2010, the sika deer population locally living on the territory of the Czech Republic occupied 55 thousand ha of new territories every year, on average. These results correlate with the findings of studies by Dvořák et al (2014) …”
Section: Resultssupporting
confidence: 83%
“…So in the period 2003 -2010, the sika deer population locally living on the territory of the Czech Republic occupied 55 thousand ha of new territories every year, on average. These results correlate with the findings of studies by Dvořák et al (2014) …”
Section: Resultssupporting
confidence: 83%
“…Some studies on the home range of deer have used the Brownian Bridge Model [ 35 ] (1163 ha) and MCP 100 % (280 ha [ 98 ], 2.69–17.55 ha [ 99 ]). It was observed that the male home ranges were more extensive than those of females [ 2 , 68 , 86 , 93 , 99 , 100 ], with an average ratio of 1.94 ± 0.25 ( Appendix A ) and a more extensive home range in winter (74–197 ha) than in summer (66–125 ha) [ 85 ].…”
Section: Resultsmentioning
confidence: 99%
“…The deer in the survey area had a mean UD of 66.831 ± 15.241 ha using the MCP approach and 78.324 ± 20.82 ha using the KD approach. The estimation process and constraints are different for each UD estimation method [ 35 , 40 , 84 ]. This study assessed UD solely using MCP and KD (at a bandwidth of 123.99) approaches that were statistically similar to those verified by the KS test for female deer.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations